2017
DOI: 10.1371/journal.pone.0182563
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between atherosclerosis and occlusal support of natural teeth with mediating effect of atheroprotective nutrients: From the SONIC study

Abstract: Whereas most of studies investigating relationship between oral health and atherosclerosis have focused on periodontitis, very few of them were examined about occlusal status of natural teeth which possibly influence dietary habit. The primary aim of this cross-sectional study was to investigate the association between the occlusal support of posterior teeth and the prevalence of atherosclerosis in community-dwelling septuagenarians. Also, the second aim was to test the hypothesis that the intake of key nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Periodontal condition was evaluated using periodontal pocket depth (PPD). We measured all remaining teeth of participants, and periodontal condition was categorised into 4 groups, according to deepest PPD of participants: PPD 3 mm or less, PPD 4 or 5 mm and PPD 6 mm or more …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontal condition was evaluated using periodontal pocket depth (PPD). We measured all remaining teeth of participants, and periodontal condition was categorised into 4 groups, according to deepest PPD of participants: PPD 3 mm or less, PPD 4 or 5 mm and PPD 6 mm or more …”
Section: Methodsmentioning
confidence: 99%
“…We measured all remaining teeth of participants, and periodontal condition was categorised into 4 groups, according to deepest PPD of participants: PPD 3 mm or less, PPD 4 or 5 mm and PPD 6 mm or more. 16 The bilateral maximal occlusal force was measured using pressure-sensitive sheets (Dental Prescale 50H R type; GC, Tokyo, Japan). The participants performed maximal clenching in the intercuspal position with the sheet placed between their upper and lower dental arches.…”
Section: Oral Functionsmentioning
confidence: 99%
“…Two diagnostic modalities to predict the condition of IAN, the close relationship of tooth and canal, and the close relationship to the buccolingual position were compared by non-parametric Wilcoxon matched-pairs signed-ranks test [ 13 ] followed by Tukey’s post hoc test considering the critical value of the studied range [ q ] >4.136 ( http://elvers.us/stats/tables/qprobability.html ; number of means: 3; degree of freedom: 1,000; comparing with “hypothetical gold standard”) at a significant level [ 14 ]. The association of procedural factors and demographic factors with IAN sensory impairment was compared by non-parametric Mann-Whitney U test [ 4 ] followed by Tukey’s post hoc test considering q >4.136 at a significant level (number of means: 3; the degree of freedom: 956, compared with “hypothetical gold standard”) [ 14 ]. The results were considered significant at a 99% confidence level [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The dental examination was conducted at the baseline and followup visits by four calibrated dentists. According to the results of the dental examinations, POSS without dentures at the baseline and follow-up visits was categorized into one of three groups based on the number of Occlusal Support Zones (OSZ) present in accordance with Eichner's Index, reflecting the occlusal contacts of the existing natural teeth or fixed prostheses in the premolar and molar regions [12,17,18 ]. The POSS criteria for the subjects were as follows:…”
Section: Dental Examinationmentioning
confidence: 99%
“…They reported oral health problems such as missing teeth and ill-fitting dentures as factors affecting the ingestion stage [4]. Previous studies evaluated the relationship between oral health problems and nutrition intake based on the number of remaining and missing teeth [5][6][7][8], chewing function [9], periodontal disease [10], and occlusal status [11][12][13][14][15]. Kazuya M reported that factors related to the malnutrition of elderly individuals were aging effects, social factors, psychological factors, and disease factors [16].…”
Section: Introductionmentioning
confidence: 99%